Pengaruh Literasi Keuangan, Gaya Hidup, dan Pengguna E-Wallet Terhadap Perilaku Konsumtif Mahasiswa Penerima Beasiswa Pemerintah di Sidoarjo - Nur Fadilah; M. Mustaqim; Achmad Zaki; Devika Cherly Putrihadiningrum (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of financial literacy, lifestyle, and e-wallet users on consumer behavior in government scholarship recipients in Sidoarjo. The background of this study is based on the increasing use of e-wallets and consumer lifestyle trends among students including scholarship recipients. This study uses a quantitative method with multiple regression analysis. The population in this study were 100 Sidoarjo government scholarship recipients who were used as respondents using the random sampling method. Data were analyzed using SPSS version 25. The results showed that financial literacy did not have a significant effect on student consumer behavior. However lifestyle has a positive effect on consumer behavior meaning that the higher a person's lifestyle the higher the consumption. E-wallet users also have a positive effect on consumer behavior indicating that the ease of digital transactions can improve student consumption patterns. Simultaneously, these three variables affect the consumer behavior of scholarship recipients. These results provide insight for the government and educational institutions in designing student financial management policies.